Multi-sensor measurements of titanium alloy surface texture formed at subsequent operations of precision machining process. (January 2017) - Niemczewska-Wójcik, Magdalena
Graphical abstract: Highlights: Titanium alloys were processed in the operations of abrasive precision machining. Surface topography was studied using multi-sensor measurement technologies. Multi-scale analysis allows for the comprehensive assessment of the surface texture. Surface texture and its functional properties depends on machining conditions. Cracks, dales/dents, scratches have impact on the surface functional properties. Abstract: The paper presents the issues concerning difficult-to-machine materials along with machining process and technologies used to measure surface topography. Thorough research comprising precision machining process and multi-sensor measurements enabled multi-scale analysis of surface texture. The subjects of the study were titanium alloys TiAlSiZr. The semi-finished products were subjected to precision abrasive machining process which consisted of preliminary grinding, precision grinding, lapping, and polishing. The surface texture obtained after each operation of machining process was measured using a white light interference microscopy, a scanning electron microscopy and an atomic force microscopy. The measurement results obtained from the multi-scale analysis show differences in the surface texture of titanium alloys, resulting mainly from machining conditions including the applied tools (grains and micrograins of diamond). Surface defects, e.g. grinding cracks (preliminary grinding), dales of different geometry (precision grinding), scratches and the distribution of dales/dents (lapping and polishing) influencing surface functional properties were discussed.